Heat and mass exchanging processes in a refrigerated truck body during multi-drop urban distribution of fresh herbs - N. Kornienko, Vladimir (2020)
The article presents the results of a study on heat and mass transfer processes in a refrigerated truck body with frequent door openings typical for multi-drop urban distribution, and their effect on microbiological indicators and chemical composition of transported fresh herbs. A refrigerated body with an isothermal body of 11 m3 capacity fixed to Gazelle truck chassis loaded with dill and parsley as transport cargo were used in a two-stage experiment. The changes in air parameters (temperature, velocity, relative humidity) in various parts of the body were determined depending on the door opening duration when unloading part of the product. The heat gain and the amount of condensate from the intake of outside air through the open door were calculated based on the experimental data obtained in an empty truck body, and their effect on microbiological indicators and the chemical composition of greens was determined based on laboratory data obtained after transportation and storage in a commercial refrigerator. It was established that the amount of heat entering the body through an open door in 10 minutes is comparable to the heat gain through its insulated walls when the door is closed for two hours. 45% of heat and 70% of moisture came into the truck body in the first two minutes of door opening. After the transportation and pre-sale storage with a total duration of 78 hours, a sharp microbial growth was observed. The number of bacteria increased 5-6 times on parsley, and 3-4 times on dill; besides, parsley and dill showed a 10 fold increase in fungi and yeast on their surface, respectively. Over a similar period of time, the same indicators of fresh herbs not subjected to the transportation and stored in a refrigerator at stable temperature and humidity conditions increased only 2 times. It has been shown that fluctuations in temperature and humidity in the truck body also lead to a change in the chemical composition of greens during further cold storage before sale. The obtained data on heat gain during door opening time must be taken into account when calculating the capacity of the truck refrigeration unit.